Preservation of fish using instant extract of green and black tea - Tutun Nugraha; Anthony Fernando; Pudjo Rahardjo (Jurnal Penelitian Teh dan Kina, 2012)
The use of illegal and hazardous preservative agents such as formalin by traditional fishermen and trader has become a problem in Indonesia.  In this research, instant extract powder of green tea and black tea were used as natural preservatives for fish. Both substances are known for their anti-bacterial and anti-oxidative activities due to the presence of various types of polyphenols, particularly the catechin groups. The tea extract powder was produced  by drying  using a spray drying device. The two different tea extract powders were tested separately, and in combination. The tests were done by dipping pieces of fresh indian mackerel fish (Rastrelliger kanagurta), also known locally as kembung banjar, in the solution containing the tea extract. The microbial tests were done using total plate count (TPC) method. The result showed that instant green and black tea extracts was capable in suppressing bacterial growth in fish. When the two substances were mixed together, the preservation activities were found to be stronger than if they were used separately. In addition, histamine and total volatile base nitrogen (TVB-N) tests which are regularly used to test the freshness of fish also showed substantial improvement in the quality of the fish sample. The sensory tests also showed that the extracts were capable of improving the freshness of the fish sample.